2000
DOI: 10.1034/j.1399-3003.2000.16f13.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum eosinophils and neutrophils and bronchiectasis severity in allergic bronchopulmonary aspergillosis

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a hypersensitivity reaction to the fungus Aspergillus fumigatus that may progress to bronchiectasis. The aim of the present study was to characterize airway inflammation in patients with clinically stable ABPA and asthma, and to correlate this with bronchiectasis severity.Subjects with ABPA and central bronchiectasis (ABPA-CB; n=16) and ABPA with serological evidence alone (ABPA-S; n=10) were studied. Comparison groups were A. fumigatus-sensitized asthma (n=19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 24 publications
3
53
0
2
Order By: Relevance
“…1B. The inflammatory pattern in BALB/c mice was reminiscent of the neutrophil-rich inflammation in severe asthma and ABPA (6,20), which persuaded us to investigate the underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B. The inflammatory pattern in BALB/c mice was reminiscent of the neutrophil-rich inflammation in severe asthma and ABPA (6,20), which persuaded us to investigate the underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillus fumigatus, which induces allergic bronchopulmonary aspergillosis (ABPA) in 25% of severe asthmatics, is one of the most common fungi involved (1,2). Neutrophilic airway inflammation is now well recognized as being a feature of severe asthma (3)(4)(5) and ABPA (6,7). During acute infection, neutrophils are crucial for antifungal defense (8,9), and lack of neutrophils is the best appreciated risk factor for invasive aspergillosis (10).…”
Section: Th17 | Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Adults with stable asthma were recruited from the respiratory clinic of the John Hunter Hospital and classified as ABPA (n=29) or non-A. fumigatus-sensitised asthma (n=9), as previously described [5]. Twenty-one healthy controls were recruited by advertisement.…”
Section: Subjectsmentioning
confidence: 99%
“…ABPA is typically characterised by sputum eosinophilia, however, lung tissue also shows a mixed inflammatory infiltrate with eosinophils and neutrophils [4]. Recently the current authors reported that sputum neutrophils were increased in ABPA and correlated with the severity of bronchiectasis [5].…”
mentioning
confidence: 93%